Division of Labour and Directed Production - Marisa Ratto; Wendelin Schnedler (University of Heidelberg, Department of Economics, 2005)
We examine a situation where efforts on different tasks positively affect production but are not separately verifiable and where the manager (principal) and the worker (agent) have different ideas about how production should be carried out: agents prefer a less efficient way of production. We show that by dividing labour (assigning tasks to different agents and verifying that agents do not carry out tasks to which they are not assigned), it is possible for the principal to implement the efficient way of production. Colluding agents can undermine this implementation. However, if agents have different abilities, collusion can be prevented by a specific assignment of agents to tasks.
Keywords: L23; M52; D82; J24; 330; hidden action; moral hazard; specialisation; job design; Anforderungsprofil; Arbeitsteilung; Prinzipal-Agent-Theorie; Moral Hazard; Asymmetrische Information; Theorie